Freshwater lamprey and fishes of Iran: Reappraisal and updated checklist with a note on Eagderi et al. (2022) - Sayyadzadeh, Golnaz; Esmaeili, Hamid Reza (Zootaxa, 2024)
This checklist aims to update the list of the inland fish fauna of Iran including newly described species and also clarify the status of some taxa including some gobies and catfishes which were ignored in the checklist provided by Eagderi et al. (2022). The checklist is arranged by classes, orders, families, and species. In total, 300 species, belonging to 110 genera, 38 families, 23 orders, and three classes were recognized from Iranian basins, with the presence of 11 reported species that need confirmation by specimens. Additional notes about the taxonomy of several taxa are provided in the discussion section.